2015
DOI: 10.7726/ajhmt.2015.1012
|View full text |Cite
|
Sign up to set email alerts
|

Transient Hydromagnetic Forced Convective Heat Transfer Slip Flow Due to a Porous Rotating Disk with Variable Fluid Properties

Abstract: In this paper we have studied the problem of an unsteady hydromagnetic forced convective heat transfer slip flow over a porous rotating disk taking into account the temperature dependent density, viscosity and thermal conductivity. The governing non-linear partial differential equations of the flow are transformed into a set of non-linear ordinary differential equations using similarity transformations. The resulting nondimensional equations have been solved numerically by applying Nachtsheim-Swigert shooting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 27 publications
(38 reference statements)
2
2
0
Order By: Relevance
“…We observe that numerical value of (0), − (0) and − (0) decreases with the increasing value of Kn, Re, and radiation parameter . Tables 2 and 3 depict the comparison of skin friction coefficients and rate of heat transfer between the results obtained in the present investigation and the literature available [33,48,49]. It is observed that results obtained in present study are very well in agreement with the existing results.…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…We observe that numerical value of (0), − (0) and − (0) decreases with the increasing value of Kn, Re, and radiation parameter . Tables 2 and 3 depict the comparison of skin friction coefficients and rate of heat transfer between the results obtained in the present investigation and the literature available [33,48,49]. It is observed that results obtained in present study are very well in agreement with the existing results.…”
Section: Resultssupporting
confidence: 85%
“…Comparison between the results of present study with the results reported by Kelson and Desseaux[48], Maleque and Sattar[33], and Alam et al[49] for rate of heat transfer − (0) for Pr = 0.71, = 0, = 0, Kn = 0, and = 0.…”
supporting
confidence: 78%
See 1 more Smart Citation
“…Kumar [17] explored the impact of the magnetic dipole on thermophoretic particle deposition, selecting Maxwell fluid over a stretching sheet. Additionally, the influence of thermophoretic particle deposition under various conditions is noticed by many authors [18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 95%